KAJIAN PERSEPSI ANGGOTA 3 (TIGA) SEKOLAH PETERNAKAN RAKYAT (SPR) DI KABUPATEN KEDIRI TERHADAP ASPEK KELEMBAGAAN DAN PEMASARAN SAPI - Anas Romzy Hibrida; Ricky Dodi Mardani; Farida Subania Dwijayanti; Didik Rudiono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to observe farmers' perception of members of the 3 SPR (People's Animal Husbandry School) groups in Kediri Regency on cattle's institutional and marketing aspects. The three SPRs fostered by UNISKA Kediri are: SPR Lembu Barokah, SPR Joyo Langgeng, and SPR Ngudi Rukun. This study used a quasi-experimental method and Completely Randomized Design (CRD) analysis with unequal replications, and further tests were carried out using the Least Significant Difference (LSD). The independent variable was the perception, and the dependent variable was the institutional and marketing aspects. The results showed that based on the cultural background, there are differences in respondent perception on institutional and marketing aspects to cattle management. Therefore, it could impact to the performance of each SPR. It is suggested to adopt the benefit of each SPR culture background to improve each SPR, respectively.